Family Support and Mother's Perception in Compliance with Providing Complete Basic Immunization for Babies (Aged 0-12 Months) in Padang, Indonesia - Ratih Septiana Arpen; Nur Hidayah Afnas (Archives of The Medicine and Case Reports, 2023)
There are around 20 million children in the world who do not receive complete immunization. One indicator of the success of a complete basic immunization program is its achievement of complete basic immunization (IDL) in Indonesia, which has reached 87.8% and needs to be increased to reach the target of 93%. This study aimed to find out family support and mothers' perceptions regarding compliance with providing complete basic immunization for babies (aged 0-12 months) in Padang. Research methods using mixed methods, quantitative using a cross-sectional approach and qualitative using a phenomenological approach, were carried out in July-August 2021, a sample of 91 people, namely babies at the Ambacang Health Center and Lapai Health Center 2021 and 17 informants. Data analysis using the Chi-square test and regression test. This logistics is to obtain and obtain a description, analysis, interpretation, and factors that most influence the complete basic immunization factors for babies at the Ambacang Health Center and Lapai Health Center, Padang. The results of the Chi-square statistical test results on maternal perception 0.000) and family support (0.020), So it can be concluded that there is an influence of family support on the mother’s perception, with the provision of complete basic immunization for babies (aged 0-12 months) in Padang. The most dominant factor affecting complete basic immunization in babies was the mother’s perception (p-value 0.000).